Nucleophilic Addition of 1,1′-Bis(hydroxymethyl)ferrocene to Alkynes: Synthesis of Ferrocene Diethenyl Ethers - Oparina, Ludmila A.; Kolyvanov, Nikita A.; Tarasova, Olga A.; Albanov, Alexander I.; Tantsyrev, Anatolii P.; Trofimov, Boris A. (Synthesis, 2020)
Chemoselective and atom-economical methods for the synthesis of ferrocene diethenyl ethers have been developed via direct base-catalyzed addition of 1,1′-bis(hydroxymethyl)ferrocene to various acetylenes. This ferrocene diol has been shown to be capable of adding to acetylene (KOH/DMSO, 70–80 °C, 1–3 h), propyne (KOH/DMSO, 70 °C, 12 h), phenylethyne (KOH/DMSO, 20–25 °C, 48 h), alkylpropiolates (DABCO, 10 mol%/CH2Cl2, 20–25 °C, 0.5 h), and acylacetylenes (DABCO, 1 mol%/CH2Cl2, 20–25 °C, 0.5 h) to afford the corresponding diethenyl ethers in 73–98% yields.
Keywords: alkynes; 1,1′-bis(hydroxymethyl)ferrocene; nucleophilic addition; diethenyl ethers; regioselectivity